Oxidative stress in children with severe acute malnutrition between 6 months to 5 years of age - Shrivastava, Komal; Gaur, Ajay; Ambey, Ravi (International Journal of Contemporary Pediatrics, 2018)
Background: Severe acute malnutrition (SAM) constitutes one of the major nutritional and health problems in children under five years of age in developing countries. It has a significant contribution to the mortality and morbidity in this age group of children. So, there is a need to look for the pathophysiology identifying events at cellular level to formulate better management strategies. The oxidative stress and a possible consequential accelerated apoptosis may contribute to pathophysiology in malnutrition. Markers of oxidative stress are Malondialdehyde levels (MDA), a byproduct of lipid peroxidation and antioxidants like Zinc and Glutathione (GSH). So the objective of study is to measure oxidative stress in hospitalized children with severe acute malnutrition (SAM) between 6 months to 5 years of age through serum levels of Zinc, glutathione and MDA. Methods: This was a hospital based prospective case control study where 100 hospitalised children from 6 months to 5 years of age with severe acute malnutrition were selected along with 100, sex and age matched healthy controls from outpatient department. Oxidative Stress was analysed by measuring serum levels of Zinc, GSH and MDA. Control group was simultaneously analysed for similar parameters of oxidative stress. Results: Serum GSH and Zinc levels were found to be significantly lower while serum MDA level was found to be significantly higher in cases as compared to controls. Conclusions: Severe acute malnourished children had an increased oxidative stress and decreased antioxidant defence compared with healthy controls.